Crime scene : a novel - Kellerman, Jonathan; Kellerman, Jesse (Kellerman, Jonathan. Clay Edison series., 2017)
"A corpse lying at the bottom of the stairs. A beautiful but troubled young woman. A brutal, decades-old murder. And the man charged with making sense of it all. Clay Edison is a former star athlete turned coroner's investigator. It's his job to care for the dead and the people they leave behind. It's not his job to solve mysteries. But some cases--and some people--can't be resisted. What he discovers will set him on a quest to overturn a hideous injustice, no matter the consequences"--